Kajian akad jual beli dalam mekanisme vending machine perspektif Fiqh Muamalah - Ramadhan, Gilang (Maliki Interdisciplinary Journal, 2025)
The concept of contract (akad) in fiqh muamalah plays a crucial role in determining the validity of transactions based on Islamic principles. Scholars define akad as an agreement between two parties that meets certain conditions and requirements, such as the clarity of the goods, price, and mutual consent of both parties. Akad is also classified into various types, such as jual beli (sale), ijarah (lease), and others. In the modern context, the mechanism of vending machines is interesting to analyze from the perspective of fiqh muamalah. Vending machines operate automatically through transaction stages, including product selection, payment, and retrieval of goods. An analysis of the akad in vending machines shows that this transaction involves elements of jual beli, with the operator acting as an intermediary between the user and the producer of the goods. The validity of the transaction in fiqh muamalah can be assessed through the fulfillment of akad conditions, such as clarity of the goods (ma’qud ‘alaih), clarity of the price (tsaman), and mutual consent (taradhi) of both parties. However, potential violations of the akad, such as goods not being dispensed or being damaged, should be considered. The opinions of scholars on automatic transactions indicate that the use of technology in muamalah is permissible as long as it does not violate Islamic principles, such as maslahah (public interest) and ease. Therefore, vending machines can be considered in accordance with fiqh muamalah as long as they meet the applicable conditions of akad